CCL18-induced HOTAIR upregulation promotes malignant progression in esophageal squamous cell carcinoma through the miR-130a-5p-ZEB1 axis. (28th September 2019) - Wang, Wenjian; Wu, Duoguang; He, Xiaotian; Hu, Xueting; Hu, Chuwen; Shen, Zhiwen; Lin, Jiatong; Pan, Zihao; He, Zhanghai; Lin, Huayue; Wang, Minghui
Abstract: Accumulating evidence indicates that CCL18 and the long non-coding RNA, HOTAIR, have critical roles in cancer progression and metastasis, but the correlation between CCL18 and HOTAIR in esophageal squamous cell carcinoma (ESCC) and their downstream molecular mechanisms remain unclear. Overexpression of CCL18 in ESCC tissues was associated with a worse survival in patients with ESCC. CCL18 enhanced the invasiveness of ESCC cells in a dose-dependent manner, whereas CCL18 knockdown inhibited their invasiveness. In particular, CCL18 expression was positively associated with HOTAIR expression in ESCC tissues. Furthermore, CCL18 upregulated the expression of HOTAIR, and knockdown of HOTAIR alleviated the CCL18-induced invasiveness of ESCC cells. HOTAIR may act as a competing endogenous RNA and could effectively becoming a sponge for miR-130a-5p, thereby modulating the derepression of ZEB1 and promoting epithelial–mesenchymal transition in ESCC. Our study suggests that CCL18 contributes to the malignant progression of esophageal cancer by upregulating HOTAIR expression. HOTAIR overexpression may promote tumor invasiveness and progression in ESCC, given that HOTAIR functions as a miR-130a-5p sponge, positively regulating ZEB1. This provides new therapeutic targets for early diagnosis and treatment of ESCC. Highlights: The first discovery of the effect of mutual regulation of CCL18 and HOTAIR on the progression of esophageal cancer. Overexpression of HOTAIR may promote tumor invasiveness and progression in ESCC by functioning as a miR-130a-5p sponge. Our findings provide new insights into the role of CCL18/HOTAIR and their downstream pathway in the development of ESCC.